IL SOGGETTO VULNERABILE E LO STATO RESPONSABILE - Fineman, Martha Albertson (Gênero & Direito, 2016)
Since there is no U.S. constitutional guarantee to basic social goods, the anti-discrimination, sameness-of-treatment approach to equality which is prevalent in the United States is particularly problematic. In this scenario, little help comes from the international context, since America has not ratified many of the international agreements concerning human rights, including those associated with the economic ones. Similarly, American courts face resistance, if not outright rejection, in applying human rights ideals: several Justices of the Supreme Court decried references to human rights principles used to bolster arguments about constitutionality under American precedent to be the application of "foreign fads" when (superior) American constitutional provisions should prevail. Fineman’s concept of vulnerability (and the related idea of vulnerable subject), initially conceived to challenge this status quo by covertly introducing the human rights discourse in the American context, is now a peculiar approach, focused on exploring the nature of the human part, rather than the rights part, of the human rights trope. Importantly, consideration of vulnerability brings societal institutions, in addition to the State and individual, into the discussion and under scrutiny: indeed, being a characteristic of a relational self, the concept suggests that institutions should be responsive to individuals. Therefore, the nature of human vulnerability forms the basis for a claim that the State must be more responsive to that vulnerability and do better at ensuring the promise of equality of opportunity.